Standar Penilaian Pendidikan - Muh. Yusuf; Rizal Awaludin; Eka Widyanti (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
Assessment is a crucial element in the educational framework, necessitating explicit and actionable standards. The Indonesian education assessment standards are outlined in Permendikbud No 23 of 2016, which is divided into 8 chapters and 15 articles. The aim of this research is to scrutinize the criteria within these education assessment standards. Employing a literature review approach and content analysis for technical examination, the study reveals that the Indonesian education assessment standards are well-defined. These standards encompass the extent, goals, advantages, foundational principles, methodologies, processes, and tools for evaluating students' academic achievements. These standards are intended to direct the assessment processes undertaken by teachers, educational institutions, and the government.